2017
DOI: 10.1002/brb3.758
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and effectiveness of levodopa‐carbidopa intestinal gel infusion

Abstract: IntroductionLevodopa‐carbidopa intestinal gel (LCIG) infusion has demonstrated to improve motor fluctuations. The aim of this study is to assess the long‐term safety and effectiveness of LCIG infusion in advanced Parkinson's disease (PD) patients with motor fluctuations and its effect in nonmotor symptoms.MethodsAdverse events (AE) and their management, clinical motor, and nonmotor aspects were assessed up to 10 years. Thirty‐seven patients were treated with LGIC; in three subsets of patients, specific batteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
8
28
2
Order By: Relevance
“…Furthermore, as expected, we found no significant changes of UPDRS‐III between preinterventional MedON and postinterventional MedON(/StimON) for all three groups . Our results also confirm studies that reported an improvement of ON‐state Hoehn and Yahr scale for STN‐DBS, IJLI, and APO . Based on dyskinesia/motor fluctuation ratios, treatments were chosen independently from these motor complication profiles.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, as expected, we found no significant changes of UPDRS‐III between preinterventional MedON and postinterventional MedON(/StimON) for all three groups . Our results also confirm studies that reported an improvement of ON‐state Hoehn and Yahr scale for STN‐DBS, IJLI, and APO . Based on dyskinesia/motor fluctuation ratios, treatments were chosen independently from these motor complication profiles.…”
Section: Discussionsupporting
confidence: 90%
“…Frequently reported AEs were associated with PEG‐J complications (mainly related to stoma‐site maintenance), comorbidities associated with advanced PD (eg, fall, fracture), aging (eg, fractures, osteoarthritis), or dopaminergic therapy (eg, dyskinesia, insomnia). The overall safety profile was like that reported in a recent integrated summary of safety of an average LCIG exposure of just more than 2 years, as well as prospective open‐label and retrospective observational studies . A total of 36 patients (14%) reported AEs related to weight loss, as was also reported in the integrated safety study (59 patients [14%]) and was similar to rates reported in a retrospective survey of more than 900 patients and a prospective open‐label routine‐care study of 59 patients .…”
Section: Discussionsupporting
confidence: 80%
“…Despite these limitations, this is the longest prospective study to date evaluating the safety and efficacy of LCIG, with an average infusion of 4.1 years. Although a high incidence of AEs was noted, long‐term use was associated with a relatively low annual discontinuation rate (average, 10% per year), with overall discontinuation rates similar to other long‐term follow‐up studies and low incidence of serious AEs.…”
Section: Discussionsupporting
confidence: 65%
“…Patients started LCIG infusion after receiving an implant of percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) following a previously described procedure used in our center [ 14 ]. The initial LCIG maintenance dose was calculated according to the levodopa equivalent daily dose; the optimal dose was titrated individually until reaching the best motor performance, controlling motor fluctuations without causing annoying dyskinesia, and getting a stable infusion for less than 16 hours a day, stopped at night, when patients received an oral nocturnal dose of levodopa.…”
Section: Methodsmentioning
confidence: 99%